The local dynamics of global ecotourism trend in the old Balinese village, Indonesia - I Wayan Suyadnya; Desi Dwi Prianti; Sanggar Kanto; I Nyoman Darma Putra (Cogent Arts & Humanities)
Ecotourism long has been regarded as a model of tourism development that fosters businesses, empowers local communities, and benefits for nature conservation. While many studies emphasize its environmentally friendly attributes, few have explored its relationship with capitalism and indigenous people. This article examines the local-global dynamics of an indigenous community in Bali, Indonesia, focusing an old-Balinese village, Tenganan Pegringsingan, and its engagement with Village Ecotourism Network (JED) project. We deployed an ethnographic discourse analysis as research methods with observation participation, interview, and discourse analysis. We challenge the assumption that global ecotourism effectively supports the economic and cultural sustainability of local populations. Our findings reveal that ecotourism has reinforced the economic interests of villagers by facilitating the spread of capitalist ideas in the development of tourist village. Instead of enhancing livelihoods, ecotourism encourages increased consumption and necessitates a re-evaluation of capital resources within the tourism sector, it has marginalized many individuals who lack resources and capital. Moreover, we suggest that the ecotourism extends beyond the confines of the economic, cultural, and conservation, an important discourse underlying this is the interplay between the shift of consumption and the idea of managing the capital, which subtly illuminates another aspect of indigenous communities.